Analysis of caesarean section rate in tertiary care hospital according to Robson`s 10 groups classification - T., Varija; C. M., Veerendra Kumar; Tarihalli, Chandrasekhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The caesarean section (CS) delivery rate is steadily increasing worldwide, including India. Identifying the proportion of women in various categories as per Robson's ten group classification system and CS rate among them is important to bring down the increasing CS rate. Methods: This case series study was conducted at Vijayanagar Institute of Medical Sciences (VIMS), a tertiary care teaching hospital in Ballari, Karnataka, India. All pregnant women who have been admitted for delivery were enrolled and the data was collected for the women delivered by CS during January 2016 to December 2016 and proportions in various groups as per Robson’s ten-group classification system were calculated. Results: Among a total of 6980 women delivered during study period, 2992 (42.8%) delivered by CS. The CS rates among various groups varied from 100% among women with abnormal lies and group 6-95% (all nulliparous breeches) group 5-94% (Previous CS, single cephalic, >37 weeks) to 10 to 15% among multiparous women with spontaneous labour having single cephalic pregnancy (group 3). Among women with previous section, CS rate was very high (89.6%). Women with previous CS (group 5) contributed maximum (40.24%) to the total number of CS. Conclusions: In the present study, all women with breech presentation and abnormal lies delivered by CS and repeat CS was the highest contributor to all CS deliveries.